SCENARIO ANALYSIS AND STRESS TESTING AS TOOLS FOR RISK ASSESSMENT IN THE GLOBAL ECONOMY - Parkhomenko, Viktoriya (Sworld-Us Conference proceedings, 2025)
The paper explores the use of scenario analysis and stress testing as tools for risk assessment in the global economy. It demonstrates that current challenges, including crises, the pandemic, military conflicts, and climate risks, require these methods to